2008
DOI: 10.1055/s-2007-965475
|View full text |Cite
|
Sign up to set email alerts
|

Der Mallet-Finger bei Kindern und Jugendlichen

Abstract: The "mallet finger" in childhood and adolescence differs from the "mallet finger" in adults because of an open or gradually closing epiphysial plate. Thus, our results of conservative and operative treatment were evaluated particularly in consideration of an open growth plate. We analysed retrospectively the data of all patients who suffered a lesion at the extensor tendon insertion between 1996 and 2005 and were treated at our hospital. The coding was done according to age, sex, localisation, typing by Doyle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
5
0
9
Order By: Relevance
“…Schmidt et al 18 in their study obtained 94% excellent results. In our study we obtained excellent results for all our patients.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Schmidt et al 18 in their study obtained 94% excellent results. In our study we obtained excellent results for all our patients.…”
Section: Discussionmentioning
confidence: 82%
“…Studies by Hart et al 5 and Schmidt et al 18 reported the most frequently observed complications were surficial skin ulcerations. In our study 2 cases developed skin problems.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Synonym werden in der englischsprachigen Literatur die Begriffe "mallet finger", "drop finger", Kricket-oder Baseballfinger verwendet, in der deutschsprachigen Literatur findet sich zuweilen der Begriff Busch-Fraktur [22].Ursache der dorsalen Endphalanxbasisfraktur ist eine auf den gestreckten Finger einwirkende axiale Kraft in der Regel im Rahmen von Ballsportarten oder der direkte Anprall des gestreckten Fingers gegen ein Hindernis [3,18,22,23]. Hierbei wird die Größe des Fragments von der Stellung des Endglieds sowie der Größe der einwirkenden Kraft zum Zeitpunkt des Traumas bestimmt [3,11,22].…”
unclassified